TEKSTUR BARU STUDI ISLAM; PROTOTIPE DIALEKTIKA AGAMA DAN REALITA - Hijrian A. Prihantoro (Millah: Journal of Religious Studies, 2016)
Islam is not mean just a religion but a civilization. The expectation for Islamic inaugural re-experience on the contemporary era is a major occupation for today's thinkers. The efforts of reconstruction of the religiousness understanding is the main idea which cannot be avoided because the event of Islamic Studies contest strives to inculcate sensitivity towards the diversity of the meaning of religious text. So, the attempts to present a new reading of the classical Islamic corpus is a necessary activity. It is intended that human values which have precipitated can be raised and be realized. If on the initial period of Islam, the Prophet PBUH and the Companions called out to create a single society, it is now the opposite; plural and multicultural. Therefore, there should be a progressive creations to transform a religiousness worship valuesas a set of humanity social values.